From Antiracism to Abolition: The Role of University Culture Centers in Black Students' Academic Identities and Language - (:unkn) unknown (My University, 2023)
Drawing on focus group, interview, and participant-observer data collected as part of this IRB-approved [19.177] qualitative research project, this dissertation provides insights about how Black American students develop academic identities through coursework and extracurricular involvement in a Black culture center on the campus of a historically white institution (HWI). I apply the lens of “abolitionist education” (Love) to explore the languaging that students and faculty in the Black culture center do to create community and racial uplift in a type of institution where racial identity historically has been marginalized and obscured—and where, the collected data indicate, such occlusion continues despite institutional efforts to prioritize diversity, equity, and inclusion. Through this analytical lens, I consider how college writing teachers who are committed to antiracism might reimagine their work as abolitionist educators. This reframe illuminates not only the nature and scope of the structural work that lies ahead for people who aim to abolish institutionalized racism in higher education but also the collaboration necessary to see it through. I conclude by offering four means by which abolitionist educators, including but not limited to writing teachers, can strengthen their impact in their own institutions.
Keywords: academic identity; belonging; Black students; college students; culture center; language